Architects' data - Neufert, Ernst; Kister, Johannes; Sturge, David
"Architects' Data provides an essential reference for the initial design and planning of a building project. Organised largely by building type it covers planning criteria and considerations of function and siting, and with over 6200 diagrams it provides a mass of data on spatial requirements. Most illustrations are dimensioned and each building type includes plans, sections, site layouts and design details. An extensive bibliography and a detailed set of metric/imperial conversion tables are included. Since it was first published in Germany in 1936, Ernst Neufert's handbook has been progressively revised and updated through 41 editions and many translations. This fifth edition of the English language version, based on the most recent German 41st edition, provides a major new edition for an international readership"--
"Originally Published in the German Language by Vieweg + Teubner, 65189 Wiesbaden, Germany, as "Ernst Neufert: Neufert Bauentwurfslehre. 41. Auflage (41st Edition)."
0
Keywords: Architecture; Building; Building -- Planning; ARCHITECTURE / Design, Drafting, Drawing & Presentation